Movement, Behavior, and Habitat Use of Whale Sharks (Rhincodon typus) in the Tropical Eastern Pacific Ocean - Guzman, Hector M.; Collatos, Caroline M.; Gomez, Catalina G. (Frontiers in Marine Science, 2022)
Whale sharks (Rhincodon typus) are found circumglobally in tropical, subtropical, and warm temperate waters, and their known seasonal aggregations and migratory movements are influenced by factors such as ocean currents, thermobiological systems, and patterns of productivity. Several locations in the eastern tropical Pacific Ocean are known habitats for R. typus; Although it has long been known that whale sharks aggregate along the Panama coast, little is known in relation to their movement patterns, behavior, and habitat use. In this study, we investigated the movements and behaviors of R. typus tagged in Panama in relation to oceanographic variables and examined the overlap of foraging habitat and migratory routes with marine protected areas (MPAs), industrial fishing areas, and marine traffic. Satellite tracks from 30 R. typus tagged in the coastal waters of Panama were examined, including nine tags suspicious of earlier detachment. A hidden Markov model was then used to identify different behavioral states (foraging and migrating) and their relationships with environmental variables (sea surface temperature, primary productivity, chlorophyll-a concentrations, and eddy location/speed) Tracks were also superimposed on maps of MPAs, industrial fishing areas, and regional marine vessel traffic to identify the degree of overlap. Rhincodon typus foraged mainly within the Panamanian exclusive economic zone but also moved north and south along the coast and out to the open ocean. Significant differences in environmental conditions were found between sites in which foraging and migrating behaviors were recorded. Higher productivity and chlorophyl concentration were associated with foraging behavior, while higher eddy speeds were observed when sharks migrated. Rhincodon typus used MPAs; however, there was a high degree of overlap between their habitat and areas of industrial fishing and marine vessel traffic. Our results highlight the use of the coastal waters of Panama, oceanic seamounts, and ridges, MPAs and industrial fishing areas by R. typus for foraging and migration. Additionally, our findings highlight the importance of satellite tracking studies for understanding the behavior and habitat use of highly mobile migratory species, such as R. typus.